Manipulating NK cellular therapy from cancer to invasive fungal infection: promises and challenges - Oh, Bernice Ling Zhi; Chan, Louis Wei Yong; Chai, Louis Yi Ann (Frontiers in Immunology, 2023)
The ideal strategy to fight an infection involves both (i) weakening the invading pathogen, through conventional antimicrobial therapy, and (ii) strengthening the defense, which is through augmenting the host immunity. This is even more so pertinent in the context of invasive fungal infections whereby the majority of patients have altered immunity and are unable to mount an appropriate host response against the pathogen. Natural killer cells fit the requirement of an efficient executioner of the host innate effector against both tumour cells and pathogens through unique targeted cell killing and in orchestration with other arms of the immune system. These characteristics, together with a wide source of extrinsic NK cells available for harvesting, make NK cells an attractive choice as adoptive cellular therapy against the fungi in invasive infection. Improved techniques in ex-vivo NK cell activation, expansion and most importantly recent advances in genetic engineering including state-of-art chimeric antigen receptor platform development have presented the opportune moment to harness this novel therapeutic as a key component of a multipronged strategy against invasive fungal infection.